Examining the expenditures and retention of money of recreational fishing along the Wild Coast, South Africa - Pyle, Michael Jonathan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Developing countries and rural communities rely heavily on the ocean for food, transport, and the sustainability of their livelihoods. While the economics of small-scale fisheries in rural areas have received much attention, there is generally less information on the economic contributions from recreational fisheries in these areas. South Africa's marine recreational fishery is large and contributes to a significant amount of economic activity. However, the retention of money from recreational fishing activities in local rural economies is unknown and thus the potential developmental benefits from this sector remain unquantified. This study examined the economic contributions from recreational fishing along the Wild Coast and retention of expenditures within the local economy. A total of 109 face-to-face economic surveys were administered during the peak recreational fishing season in December 2021. Based on the results, recreational fishing in the Wild Coast has the ability to generate R 415 446 098 in economic activity annually, however only 9.5% of this is retained within local coastal economies, which diminishes the economic contributions of the fishery to the Wild Coast region. Expenditures on items stemming from the informal collection and selling of bait and seafood, domestic work and guiding were the highest locally retained expenditures within the region. 98% of all bait and seafood was harvested and sold by local gillies, with 2% being bought through hotels (n=109). The total direct economic contribution in terms of informal harvesting was estimated at R 16 077 711 for 2021 (n= 9 601). The identification of these contributions can be used to provide recommendations for local economic development strategies which can support the recreational fishery while uplifting coastal communities that should be benefitting more from the activity.
Keywords: Ecotourism -- South Africa; Sustainable fisheries -- South Africa; Wild Coast Region; Small-scale fisheries Economic aspects -- South Africa; Socioeconomic development; Leakage